2021
DOI: 10.1016/j.cmi.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired pneumonia severity assessment tools in patients hospitalized with COVID-19: a validation and clinical applicability study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…5 Furthermore, independent external validation has demonstrated consistent performance worldwide. 6–10 …”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, independent external validation has demonstrated consistent performance worldwide. 6–10 …”
Section: Introductionmentioning
confidence: 99%
“…These variables make up the 4C score [18]. We had demonstrated that 4C score was an accurate predictor of outcomes in our population [19]. In this present study, we did not have access to the Glasgow coma scale, and we did not use this variable for adjusted analyzes.…”
Section: Discussionmentioning
confidence: 81%
“…External validation was essential in other cohorts as well as this one since it was expected that newer scoring systems outperform older ones ( Neto et al, 2021 ). PSI and CURB-65 have been used for risk stratification and prognostic assessment in patients with COVID-19 previously ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%